2007
DOI: 10.1002/cphc.200700238
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Platinum‐Ruthenium Catalyst for Electrooxidation of Methanol by Crystalline Ruthenium Dioxide

Abstract: The fuel cell is currently being established as a future 'green' energy source. The direct methanol fuel cell (DMFC) uses aqueous methanol solution as a fuel and has potential application in mobile electronics.[1] However, the high electrocatalyst cost and poor anode performance are two key handicaps which restrain the commercialization of DMFC. [2,3] The fabrication of low-loaded but active Pt catalysts for the anode is essential for the DMFC development. Practical approaches include 1) a decrease in the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
1
40
0
1
Order By: Relevance
“…[6,29,30] The Pt/Ru bimetallic system plays an important role in energy production and storage technologies, such as direct methanol fuel cells (DMFC). [7,8,10,33,34] Although catalysts in such architectures have been widely studied, [12,28,29] the detailed atomic structure and the surface activity on methanol oxidation are still not well understood. Hence, the purpose of the present paper is to identify the evolution of atomic structure and the corresponding surface activity of core-shell type electrocatalysts with just a few ALs of Pt atoms coated on the Ru nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6,29,30] The Pt/Ru bimetallic system plays an important role in energy production and storage technologies, such as direct methanol fuel cells (DMFC). [7,8,10,33,34] Although catalysts in such architectures have been widely studied, [12,28,29] the detailed atomic structure and the surface activity on methanol oxidation are still not well understood. Hence, the purpose of the present paper is to identify the evolution of atomic structure and the corresponding surface activity of core-shell type electrocatalysts with just a few ALs of Pt atoms coated on the Ru nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The bifunctional effect is often cited to explain the promotion of specific current density (I SC ) and CO tolerance on electrocatalyst system of Pt-M NPs (M denotes the hydrophilic transition metals). Typical examples include the alloyed NPs of PtRu, [7,8] multi-element NPs of Fe 3 O 4 /Au/Pt, [9] and Pt-based catalysts supported by different matrices. [10,11] The promotion of catalytic activity on such materials originates from the formation of surface MÀ (OH) ads /MÀhydrate that provides low-energy reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, air treatment of the PtRu/Ce 10 C samples resulted in a surface composed of RuO 2 and AO x . Huang et al [22,23] and Wang et al [15] have reported that the electroactivity can be improved by the presence of Ru c O 2 . However, the air treatment has a negative effect on the electroactivity in this study.…”
Section: Enhancement Of the Activity Of Ptru/ce 10 C Catalysts By Heamentioning
confidence: 97%
“…Steigerwalt et al [21] found that the presence of oxidized Ru species in PtRu catalysts resulted in an enhanced DMFC performance. Huang et al [22,23] demonstrated that Ru atoms segregate to the surface of bimetallic crystallites and are oxidized to crystalline RuO 2 at oxidation temperatures above 520 K. Guo et al [24] indicated that the oxygen atoms released by CeO 2 particles can easily react with unalloyed surface Ru atoms. The released oxygen species can then form RuO x compounds, which improve the electrocatalytic activity, thus leading to methanol decomposition.…”
Section: Introductionmentioning
confidence: 98%